2013
DOI: 10.1099/ijs.0.046011-0
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium aroidearum sp. nov., a soft rot pathogen with preference for monocotyledonous plants

Abstract: Several pectolytic bacterial strains, mainly isolated from monocotyledonous plants and previously identified as Pectobacterium carotovorum, were thought to belong to a novel species after several taxonomic analyses including DNA-DNA hybridization. In 16S rRNA gene sequence analyses, these strains had a similarity of .97.9 % to the 16S rRNA gene sequence of strains representing six other pectobacterial species and subspecies. These strains, represented by strain SCRI 109 T , also showed some unique chemotaxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 21 publications
2
58
0
8
Order By: Relevance
“…Two strains that are considered to be type strains of two Pectobacterium species, PC1 (P. aroidearum) and Pcb1692 (P. carotovorum ssp. brasiliense), were used in this study (Nabhan et al, 2013;Onkendi and Moleleki, 2014). Pathogens belonging to these species are able to infect monocot and dicot hosts of agricultural importance, especially under warm conditions (Nabhan et al, 2012(Nabhan et al, , 2013Onkendi and Moleleki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Two strains that are considered to be type strains of two Pectobacterium species, PC1 (P. aroidearum) and Pcb1692 (P. carotovorum ssp. brasiliense), were used in this study (Nabhan et al, 2013;Onkendi and Moleleki, 2014). Pathogens belonging to these species are able to infect monocot and dicot hosts of agricultural importance, especially under warm conditions (Nabhan et al, 2012(Nabhan et al, , 2013Onkendi and Moleleki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the Pectobacterium carotovorum strains PC11 and WPP14, as well as the Pectobacterium aroidearum strain PC1 were more tolerant. The strain PC1 was once considered to belong to P. carotovorum, but was recently re-classified as P. aroidearum, a monocot specializing species [39,47]. This specialization could be at least in part attributed to the high tolerance of this Pectobacterium strain to most of the phenolic compounds.…”
Section: Growth Of Bacteria In Response To Phenolic Compoundsmentioning
confidence: 97%
“…subsp. carotovorum (Ma et al , ; De Boer et al , ; Nabhan et al , , ). The genus Dickeya is a diverse group consisting of five genomic species, that is, D. zeae , D. paradisiaca, D. dadantii , D. chrysanthemi and D. dianthicola (Samson et al , ; Brady et al , ) and new proposed species ‘ D. solani ’ (Sławiak et al , 2009 b ; Toth et al , ), all except the first two were found in association with potato in Europe (Sławiak et al , 2009 b ; Toth et al , ).…”
Section: Discussionmentioning
confidence: 99%